To What Extent Do Musculoskeletal Ultrasound Biomarkers Relate to Pain, Flexibility, Strength, and Function in Individuals With Chronic Symptomatic Achilles Tendinopathy? - Lalumiere, Mathieu; Perrino, Sarah; Nadeau, Marie-Josée; Larivière, Christian; Lamontagne, Martin; Desmeules, François; H. Gagnon, Dany (Frontiers in Rehabilitation Sciences, 2021)
Introduction: Achilles tendinopathy is a chronic musculoskeletal pathology best evaluated by ultrasound imaging. The present cross-sectional study aimed at better understanding the relationship between musculoskeletal ultrasound biomarkers (MUBs) of Achilles tendon and localized pain, ankle flexibility, ankle strength, and functional abilities. Method: Forty-one participants with unilateral midportion chronic Achilles tendinopathy had their tendon images analyzed bilaterally in the longitudinal and transverse planes. The Victorian Institute of Sport Assessment-Achilles questionnaire and Lower Extremity Functional Scale assessed pain and function, respectively, during standing and walking-related activities. Ankle flexibility was evaluated using weight-bearing lunge tests while ankle isometric peak strength was measured using an instrumented dynamometer. Achilles tendons ultrasonographic images were analyzed using geometric (thickness), composition (echogenicity) and texture (homogeneity) MUBs. Discriminative validity was evaluated using paired Student’s t-tests to compare MUBs between symptomatic and asymptomatic sides. Predictive validity was evaluated by computing Pearson product-moment correlations coefficient between MUBs and pain, ankle flexibility, ankle strength and function. Results: Significant differences were found in MUBs between the symptomatic and asymptomatic sides, confirming discriminative validity of the selected MUBs. On the symptomatic side, thickness was found 29.9% higher (p<0.001), echogenicity 9.6% lower (p<0.001), and homogeneity 3.8% higher (p=0.001) when compared to the asymptomatic side. However, predictive validity was scarcely confirmed, as most of the correlation coefficients were found negligible for the associations investigated between MUBs with localized pain, ankle flexibility, strength and function. In fact, only fourteen statistically significant low to moderate associations were found, with negative and positive correlations ranging between -0.31 and -0.55 and between 0.34 and 0.54, respectively. Discussion: MUBs have a clinical utility in visualizing in vivo tendon integrity and diagnosticating. Achilles tendinopathy. MUBs should be valued as part of a comprehensive neuro-musculoskeletal assessment as they complement pain, flexibility, strength, and function measures. Altogether, they may inform the development and monitoring of personalized rehabilitation treatment plan.